2016
DOI: 10.21608/ejabf.2016.2288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mono or polyculture systems on water quality, growth performance and economic efficiency of Oreochromis niloticus (Linnaeus, 1758) and Hypophthalmichthys molitrix (Valenciennes, 1844)

Abstract: The aim of this study was to investigate the effect of the graded replacement of stocking density rate (0, 4, 8 and 12%) of the monosex Oreochromis niloticus by the silver carp, Hypophthalmichthys molitrix as a mono (T 1 ) or poly-culture systems (T 2 , T 3 , and T 4 , respectively) for 124 days (4 months) on water quality parameters, growth performance and feed efficiency parameters, condition factor, fish organs indices, fish body composition. The total production of O. niloticus and economic efficiency par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…2) in the present study. Furthermore, improvements in the body composition of fish reared in polyculture compared to fish reared in monoculture conditions are previously reported (Khalil et al, 2008;Mehrim et al, 2016). In the same line with the current findings, Mehrim et al (2018) reported that the body composition of O. niloticus reared in polyculture systems significantly improved compared to those reared in monoculture system.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2) in the present study. Furthermore, improvements in the body composition of fish reared in polyculture compared to fish reared in monoculture conditions are previously reported (Khalil et al, 2008;Mehrim et al, 2016). In the same line with the current findings, Mehrim et al (2018) reported that the body composition of O. niloticus reared in polyculture systems significantly improved compared to those reared in monoculture system.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies indicate that polyculture system gives the highest growth performance and survival rate of reared fish species compared to those in monoculture system (El-Sagheer et al, 2008; Mehrim et al, 2016Mehrim et al, , 2018 et al, 2001). Several studies showed the importance of determining the appropriate stocking density, especially in polyculture system, which is reflected in their productivity and profitability (Uddin et al, 2007;Abdel-Hakim et al, 2014;Shoko et al, 2016).…”
mentioning
confidence: 99%